Nursing-based precision assessment of nutrition and muscle status without ultrasound: a prospective observational study in mechanically ventilated neurosurgical patients - Pan, Chenliang; Xu, Dingding; Wang, Zixin; Wen, Jia; Ma, Lili; Zhang, Yajuan (Frontiers in Medicine, 2026)
BackgroundCritically ill neurosurgical patients on prolonged mechanical ventilation rapidly develop muscle wasting and malnutrition that hinder weaning and recovery. Ultrasound is useful but not always available for routine nursing assessment. We evaluated whether nurse-led, routinely available indicators can reflect muscle status and complement ultrasound monitoring.MethodsWe conducted a single-center prospective observational study in one neurosurgical intensive care unit (NICU) from January to October 2025. Adults expected to remain in ICU for at least 7 days and on mechanical ventilation for at least 7 days were enrolled; 137 patients were analyzed. Nutrition-related indicators included the mNUTRIC score, serum albumin, and total protein. Muscle-related measures were recorded on ICU days 1, 3, and 7 and included quadriceps and rectus femoris thickness or cross-sectional area, the Medical Research Council score, diaphragm thickness at end-expiration and end-inspiration, diaphragm thickening fraction, diaphragmatic excursion, gastrocnemius indices, and bilateral lower-limb circumference.ResultsDuring the first ICU week, peripheral muscle parameters—quadriceps, rectus femoris, and gastrocnemius—and respiratory muscle parameters—diaphragm thickening fraction, diaphragmatic excursion, and diaphragm thickness—declined significantly, consistent with early muscle wasting under mechanical ventilation. Nutritional risk increased in parallel, with decreases in albumin and total protein. The mNUTRIC score showed significant negative correlations with 13 muscle-related parameters, and albumin and total protein were positively correlated with diaphragm thickening fraction and lower-limb circumference (all p < 0.05).ConclusionIn NICU patients ventilated for at least 7 days, muscle mass and diaphragm function deteriorate early and accompany rising nutritional risk. Nurse-led indicators—mNUTRIC, albumin, and total protein—provide pragmatic screening for muscle wasting and can flag patients needing intensified nutrition or rehabilitation, while ultrasound remains indispensable for high-precision decisions such as weaning evaluation. A tiered assessment strategy may enhance applicability across ICUs with diverse resources.